PENGARUH KEADILAN ORGANISASIONAL TERHADAP MOTIVASI DAN KINERJA KARYAWAN - I Gede Nyoman Carlos Wiswanatha Mada; Desak Ketut Sintaasih; Made Subudi (Forum Manajemen STIMI Handayani Denpasar, 2017)
Human resources (HR) plays an important role for the success of a company. The purpose of this study was to assess the effect of organizational justice on the motivation and performance of employees. The study was conducted at PT. Tunas Jaya Sanur engaged in the construction of buildings with a sample of 136 employees were taken using proportionate random sampling technique. Companies must be supported with good human resource and quality to maintain the viability of the company. Analysis techniques used in this study is partial least square (PLS). The results showed that organizational justice and significant positive effect on motivation. Organizational justice is also positive and significant impact on performance. the motivation to have a positive effect on performance. The results of this study prove that, the better the perceived organizational justice by employees, motivation and performance will also increase. Similarly, the higher the motivation for good organizational justice the higher the performance of employees. The results are consistent with the theory that employees get organizational justice will increase the motivation and high performance in the completion of their duties. The practical implications of this research can be considered firm or management in making decisions or making policies - policies related to organizational justice in order to improve the motivation and performance of employees.